An integrated corporate governance index for Spain: From construction to construct validity - Paolo Saona; Laura Muro; Erika López-Quesada (Revista de Contabilidad: Spanish Accounting Review)
This study, based on agency theory, focuses on the measurement of corporate governance in the Spanish corporate sector. Its aim is to develop, evaluate and validate a specific corporate governance index that overcomes the limitations of previous research, which relies on aggregated and unvalidated measures. The research questions are: How can corporate governance in Spain be adequately measured? And how well does the proposed index represent the relevant aspects of corporate governance? These questions lead to the sub-question of the validity of the sub-indices that make up the index in relation to specific aspects of corporate governance. The study analyses a sample of 130 Spanish listed companies with 1,039 observations corresponding to the period from 2007 to 2018. An aggregate corporate governance index is constructed, composed of four sub-indices: compliance with good governance codes, ownership characteristics, board characteristics and transparency of accounting information. The results show that both the overall index and the sub-indices are positively related to firm value. Methods such as Cronbach's alpha coefficient for internal consistency and Principal Component Analysis (PCA) for index structure are used to validate the index. In addition, panel data analysis using the GMM method is employed, incorporating a novel measure of firm value that takes into account the replacement cost of assets. This study fills a gap in the literature by constructing and validating a specific index for Spain, while addressing econometric issues such as endogeneity and unobservable heterogeneity. In practical terms, the index can support the implementation of the United Nations 2030 Sustainable Development Agenda, which promotes the adoption of good governance codes. Finally, it is suggested that future research should focus on creating and validating robust indices to assess the quality of corporate governance in other contexts, thereby promoting best practices globally.